CpG DNA as a vaccine adjuvant. (April 2011) - Bode, Christian; Zhao, Gan; Steinhagen, Folkert; Kinjo, Takeshi; Klinman, Dennis M
Synthetic oligodeoxynucleotides (ODNs) containing unmethylated CpG motifs trigger cells that express Toll-like receptor 9 (including human plasmacytoid dendritic cells and B cells) to mount an innate immune response characterized by the production of Th1 and proinflammatory cytokines. When used as vaccine adjuvants, CpG ODNs improve the function of professional antigen-presenting cells and boost the generation of humoral and cellular vaccine-specific immune responses. These effects are optimized by maintaining ODNs and vaccine in close proximity. The adjuvant properties of CpG ODNs are observed when administered either systemically or mucosally, and persist in immunocompromised hosts. Preclinical studies indicate that CpG ODNs improve the activity of vaccines targeting infectious diseases and cancer. Clinical trials demonstrate that CpG ODNs have a good safety profile and increase the immunogenicity of coadministered vaccines.